Rise of the drama - Martin, Florence Adelia (My University, 1898)
Introduction: Aristotle says drama is irritated action. A common means of irritation by all peoples, is by gesture and voice. The first step toward a drama is to assume a real or fictitious character, but the true drama is not reached until irritation extends to action. The drama gratifies the wish of all men to see their life portrayed in the life of others. A requisite of the drama is unity of action; that is, everything in it should be grouped in the direction of a single end or purpose. Almost all nations had a drama of some kind though it did not always reach a permanent form in literature. The Hebrew writings partook of the dramatic feature, and of their work, we have today, the Book of Job and the Book of Ruth. It is due to the Greeks that the drama first attained its literary form. Aristotle says Homer prepared the way for the drama; by display of power in both grave and tragic lines, which suggested plots and devices for dramatic subjects. The Greek drama is of a religious origin, growing out of the songs and dances given in honor of the god of wines, Dionysus. This religious form it never lost. The drama presented two main features, the choruses and the dialogue. The chorus was an important part, and was sung between the acts. Its purpose was to reflect on the action that was going on, and to represent in verse the sentiments of the poet as spokesman. Later on, the dialogue formed the more important feature of the dramatic entertainment.
Citation: Martin, Florence Adelia. Rise of the drama. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Aristotle; Drama; Action; Greeks; Dialogue; Chorus; Theses; Manuscripts (documents)